Reinforcement Learning and Its Applications in Modern Power and Energy Systems: A Review - Di Cao; Weihao Hu; Junbo Zhao; Guozhou Zhang; Bin Zhang; Zhou Liu; Zhe Chen; Frede Blaabjerg (Journal of Modern Power Systems and Clean Energy, 2020)
With the growing integration of distributed energy resources (DERs), flexible loads, and other emerging technologies, there are increasing complexities and uncertainties for modern power and energy systems. This brings great challenges to the operation and control. Besides, with the deployment of advanced sensor and smart meters, a large number of data are generated, which brings opportunities for novel data-driven methods to deal with complicated operation and control issues. Among them, reinforcement learning (RL) is one of the most widely promoted methods for control and optimization problems. This paper provides a comprehensive literature review of RL in terms of basic ideas, various types of algorithms, and their applications in power and energy systems. The challenges and further works are also discussed.